Toward better blockchain-enabled energy trading between electric vehicles and smart grids in Internet of Things environments: a survey - Aoudia, Meriem; Alaraj, Mustafa B. M.; Abu Waraga, Omnia; Mokhamed, Takua; Abu Talib, Manar; Bettayeb, Maamar; Nasir, Qassim; Ghenai, Chaouki (Frontiers in Energy Research, 2024)
With the rise of the 3Dsdecarbonization, decentralization, and digitalization, the number of electric vehicles is projected to increase, necessitating the implementation of modern technologies to avoid unnecessary energy wastage. Numerous studies have been developed proposing electric vehicle (EV) charging frameworks in networks empowered by renewable energy resources. In addition, more focus has recently been directed on incorporating blockchain technology to assure security and transparency in trading systems. However, fewer studies have delved into developing a practical implementation of their solution due to the complexity of the topic. Therefore, this paper thoroughly investigates integrating blockchain technology in electric vehicle charging systems, analyzing the existing practical implementation and their characteristics. It studied 48 relevant studies between 2017 and 2023 covering the following main research areas: (i) renewable energy-based electric charging systems, (ii) blockchain frameworks used in energy trading, and (iii) Performance metrics of simulated and implemented solutions. Results show that blockchain applications in EVs and energy trading systems are highly current, and researchers are actively exploring ways to improve their efficiency and effectiveness.